2022
DOI: 10.1002/adma.202109609
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Nanoerythrosome‐Coated Aptamer–DNA Tetrahedron/Maytansine Conjugates: pH‐Responsive and Targeted Cytotoxicity for HER2‐Positive Breast Cancer

Abstract: DNA materials have emerged as potential nanocarriers for targeted cancer therapy to precisely deliver cargos with specific purposes. The short half‐life and low bioavailability of DNA materials due to their interception by the reticuloendothelial system and blood clearance further limit their clinical translation. This study employs an HER2‐targeted DNA‐aptamer‐modified DNA tetrahedron (HApt‐tFNA) as a drug delivery system, and combines maytansine (DM1) to develop the HApt‐DNA tetrahedron/DM1 conjugate (HApt‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
122
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(133 citation statements)
references
References 58 publications
1
122
0
Order By: Relevance
“…As a nanomaterial, DNA exhibits lots of strengths: stability, specificity, programmability, and biocompatibility. [4][5][6] Taking these great advantages, DOI: 10.1002/advs.202200327 DNA nanotechnology has moved from proof-of-concept structural constructs to biological applications. For example, DNA sequence programmability allows scientists to design precise nanostructures to fabricate many biosensors with the aid of the strict "Waston-Crick" pairing principle.…”
Section: Introductionmentioning
confidence: 99%
“…As a nanomaterial, DNA exhibits lots of strengths: stability, specificity, programmability, and biocompatibility. [4][5][6] Taking these great advantages, DOI: 10.1002/advs.202200327 DNA nanotechnology has moved from proof-of-concept structural constructs to biological applications. For example, DNA sequence programmability allows scientists to design precise nanostructures to fabricate many biosensors with the aid of the strict "Waston-Crick" pairing principle.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrahedral frame nucleic acid (tFNAs) is a new type of nucleic acid nanomaterials, which is self‐assembled through strict base pairing 20–22 . Compared with other nanocarriers, tFNAs has good biocompatibility, biodegradability, and biosafety 23,24 . Compared with single‐strand DNA, which needs the assistance of other carriers to enter the cell, tFNAs can enter the cell through the formed three‐dimensional structure, and it can achieve lysosomal escape and targeted localization by connecting specific nucleic acid sequences 25–27 .…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 21 , 22 Compared with other nanocarriers, tFNAs has good biocompatibility, biodegradability, and biosafety. 23 , 24 Compared with single‐strand DNA, which needs the assistance of other carriers to enter the cell, tFNAs can enter the cell through the formed three‐dimensional structure, and it can achieve lysosomal escape and targeted localization by connecting specific nucleic acid sequences. 25 , 26 , 27 In recent years, an increasing number of researchers have applied tFNAs to tissue regeneration engineering to explore its multiple effects on cell biological behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the efficacy would be enhanced while the adverse effects would be alleviated. Nanotechnology has been widely exploited, introducing various nanomaterials with unique properties such as high permeate, specifical and long endurance in vivo or in vitro ( Brown et al, 2019 ; Zhang T. et al, 2020 ; Ma et al, 2022 ). Plenty of evidence shows that nanomaterials could be therapeutic molecules combining with targeted tissue directly and be drug delivery systems (DDSs) transporting the drug molecules specifically ( Brown et al, 2019 ; Ummarino et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of evidence shows that nanomaterials could be therapeutic molecules combining with targeted tissue directly and be drug delivery systems (DDSs) transporting the drug molecules specifically ( Brown et al, 2019 ; Ummarino et al, 2020 ). In addition, previous studies have demonstrated that nanomaterials have multiple bio-functions ( Zhang et al, 2021 ) [anti-tumor ( Ma et al, 2022 ), anti-inflammation ( Wang et al, 2022 ; Zhang et al, 2022 ), differentiation promotion ( Li S et al, 2021 ), immune modulation ( Qin et al, 2022 ), and neuro-protection ( Zhou et al, 2021 ; Zhu et al, 2022 )]…”
Section: Introductionmentioning
confidence: 99%